Comparison of Antioxidants in Red Ginger Powder Preparations with the Addition of Sucrose and Red Ginger Powder Preparations Without the Addition of Sucrose - Kamaluddin, Irna Diyana Kartika; Nawawi, Nurafni Maharani; Syamsu, Rachmat Faisal; Royani, Ida; Bima, Irmayanti Haidir (Poltekkes Kemenkes Palu, 2024)
Antioxidants are compounds that can inhibit oxidation reactions in the human body. Antioxidants can be obtained from food intake. Intake containing antioxidant compounds can also be found in red ginger. Red ginger is available in the form of instant powder obtained through a crystallization process using sucrose as the main agent. Granulated sugar has a sucrose content of 99.95% and functions as a sweetener as well as a crystallization agent that affects the speed of crystallization. This study aims to determine the comparison of antioxidant levels contained in red ginger powder with the addition of sucrose and without the addition of sucrose. The research design used was experimental research design by testing the comparison of antioxidant compound activity between red ginger powder added sucrose and red ginger powder without added sucrose using DPPH reagent measured by spectrophotometer. The measurement of antioxidant content showed that red ginger powder without added sucrose has a very strong IC50 value of antioxidant activity with a value of 46.12 ppm while red ginger powder without added sucrose has a weak IC50 value of antioxidant activity with a value of 205.47 ppm. The results of antioxidant activity testing on both red ginger powders were then statistically tested using the unpaired T-Test test with a p-value <0.05 which means significant. It can be concluded that there is a significant difference in antioxidant activity values ​​between red ginger powder without added sucrose and red ginger powder with added sucrose.